Проблема личности и цивилизации в творчестве Курта Воннегута - Гальцева, А.И.; Александрова, О.Н. (Культура народов Причерноморья, 2014)
В статье А.И. Гальцевой и О.Н. Александровой «Проблема личности и цивилизации в
творчестве Курта Воннегута» определены основная тематика и проблемы, затрагиваемые Куртом
Воннегутом (Kurt Vonnegut, 1922-2007) в его романах «Утопия 14» («Player Piano», 1952), «Бойня номер
пять, или Крестовый поход детей» («Slaughterhouse-Five, or The Children’s Crusade», 1969),
«Галапагосы», («Galápagos», 1985) и показано, как они отражены в творчестве писателя.
Сформулированы основные мотивы романов, очерчены острые социальные проблемы, затрагиваемые
писателем, в частности, проблема человеческой личности и цивилизации. В статье описывается
своеобразие художественного мира романов и сравнивается специфика их проблематики, образы, в
которых воплощается проблема авторской личности и современной цивилизации. Определены научная
новизна, актуальность и цель статьи. В работе используются сравнительно-типологический,
структурно-аналитический и описательный методы. У статті А.І. Гальцевої та Александрової О.М. «Проблема особистості та цивілізації у
творчості Курта Воннегута» визначені основна тематика і проблеми, втілені у романах Курта
Воннегута (Kurt Vonnegut, 1922-2007) «Утопія 14» («Player Piano», 1952), «Бойня номер п’ять, або
Хрестовий похід дітей» («Slaughterhouse-Five, or The Children’s Crusade», 1969), «Галапагоси»
(«Galápagos», 1985) і показано, як вони відображені у творчості письменника. У статті сформульовані
основні мотиви романів, відокремлені гострі соціальні проблеми, втілені письменником у творах,
особливо, проблема людської особистості і цивілізації. У статті визначається особливість художнього
світу романів і порівнюється специфіка їхньої проблематики, образи, в яких втілена проблема людської
особистості і цивілізації. Визначені наукова новизна, актуальність і мета статті. У роботі
використані порівняльно-типологічний, структурно-аналітичний і описовий методи. The article by Galtseva A.I. and Alexandrova O.N. under the title «The problem of the personality
and the civilization in the works of Kurt Vonnegut» is the attempt to define the main topic and problems
represented in the novels of Kurt Vonnegut (1922-2007) «Player Piano» (1952), «Slaughterhouse-Five, or The
Children’s Crusade» (1969), «Galápagos» (1985) to examine the problems of the personality and the
civilization in the novels and to find out how they are reflected in the works of the writer. The main motives of
the novels are formulated in the article, also the hot social problems, such as the problem of the personality and
the civilization, raised by the author, are represented. The novels of Kurt Vonnegut are the example of his
personal experience and the historical events reflected by the writer. The peculiarity of the fictional world of
Kurt Vonnegut is determined in the article. The specific character of the problems of the novels «Player Piano»,
«Slaughterhouse-Five, or The Children’s Crusade», «Galápagos» and images in which the problem of the
personality and the civilization are embedded are compared. The particularity of the image of the author is
embedded in the synthesis of his philosophical, ethical and aesthetic values. The article contains its topicality,
the scientific novelty and the aim. Such methods as comparative and typological, structural and analytical and
the descriptive method are used in the work.